2018
DOI: 10.11613/bm.2018.020706
|View full text |Cite
|
Sign up to set email alerts
|

Assessing performance in pre-season wrestling athletes using biomarkers

Abstract: IntroductionAlthough regular training introduces the desired changes in athletes’ metabolism towards optimal final performance, literature is rarely focusing on the metabolic responses off-competition. Therefore, the aim of this study was to evaluate biochemical indices during typical preseason training in wrestling athletes.Materials and methodsTwenty male freestyle and Greco-roman wrestlers (14 to 31 years) followed a typical session of the preparatory phase. Capillary blood glucose and lactate concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
2
15
0
3
Order By: Relevance
“…Our findings matched the study of N. Gill, C. Beaven and C. Cook (2005) and I. Papassotiriou and A. Nifli (2018) who emphasized higher excretion of serum creatinine in 70% of the athletes according to athlete's body mass, especially in wrestlers, while athletes with lower creatinine concentrations presumed albumin abnormality. M.S.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings matched the study of N. Gill, C. Beaven and C. Cook (2005) and I. Papassotiriou and A. Nifli (2018) who emphasized higher excretion of serum creatinine in 70% of the athletes according to athlete's body mass, especially in wrestlers, while athletes with lower creatinine concentrations presumed albumin abnormality. M.S.…”
Section: Discussionsupporting
confidence: 91%
“…Fallon, G. Sivyer, K. Sivyer and A. Dare (1999), T. Hortobagyi and T. Denhan (1989) and I. Papassotiriou and A. Nifli (2018) that resting creatinine levels are higher in athletes, especially wrestlers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bioenergetic pathways for ATP production during high intensity exercise are muscle glycogenolysis and glycolysis, culminating with the increase in lactate production, which is consistent with the result observed after the fight. However, part of the lactate produced in skeletal muscle is captured by liver cells and converted into glucose through gluconeogenesis, an important metabolic pathway for maintaining blood glucose, which justifies the decrease in plasma lactate levels after 24 hr (Adeva-Andany et al, 2014;Papassotiriou & Nifli, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…When considered, clinical and functional parameters are able to diagnose the general recovery condition of the subject. In this sense, previous studies (Cesnaitiene et al, 2015; Machado et al, 2018; Papassotiriou and Nifli, 2018) have shown that these variables also have a positive correlation with athletic performance and adequate monitoring allows the use of strategies that improve recovery and sports performance and minimize exposure to the occurrence of musculoskeletal injuries.…”
Section: Introductionmentioning
confidence: 93%